Associations between abundances of free‐roaming gamebirds and common buzzards Buteo buteo are not driven by consumption of gamebirds in the buzzard breeding season. Issue 5 (3rd May 2022) - Swan, George J. F.; Bearhop, Stuart; Redpath, Stephen M.; Silk, Matthew J.; Padfield, Daniel; Goodwin, Cecily E. D.; McDonald, Robbie A.
Abstract: Releasing gamebirds in large numbers for sport shooting may directly or indirectly influence the abundance, distribution and population dynamics of native wildlife. The abundances of generalist predators have been positively associated with the abundance of gamebirds. These relationships have implications for prey populations, with the potential for indirect impacts of gamebird releases on wider biodiversity. To understand the basis of these associations, we investigated variation in territory size, prey provisioning to chicks, and breeding success of common buzzards Buteo buteo, and associations with variation in the abundances of free‐roaming gamebirds, primarily pheasants Phasianus colchicus, and of rabbits Oryctolagus cuniculus and field voles Microtus agrestis, as important prey for buzzards. The relative abundance of gamebirds, but not those of rabbits or voles, was weakly but positively correlated with our index of buzzard territory size. Gamebirds were rarely brought to the nest. Rabbits and voles, and not gamebirds, were provisioned to chicks in proportion to their relative abundance. The number of buzzard chicks increased with provisioning rates of rabbits, in terms of both provisioning frequency and biomass, but not with provisioning rates for gamebirds or voles. Associations between the abundances of buzzards and gamebirds may not be a consequence of the greater availability of gamebirds as prey during the buzzard breeding season. Instead, the association may arise either from habitat or predator management leading to higher densities of alternative prey (in this instance, rabbits), or from greater availability of gamebirds as prey or carrion during the autumn and winter shooting season. The interactions between gamebird releases and associated practices of predator control and shooting itself require better understanding to more effectively intervene in any one aspect of this complex social‐ecological system. Abstract : Releasing gamebirds for sport shooting may influence the abundance, distribution, and population dynamics of native wildlife. Positive associations between the abundances of buzzards and pheasants may not be a consequence of the greater availability of pheasants as prey during the buzzard breeding season. Instead, the association may arise either from habitat or predator management leading to higher densities of alternative prey (in this instance, rabbits) or from the greater availability of gamebirds as prey or carrion during the autumn and winter shooting seasons.